EVALUASI PROGRAM PENGAWASAN MENGGUNAKAN BODYCAM (MODEL CIPP) - Novi Indah Earlyanti; Tiwi Prabaningrum; Yoeliastuti Yoeliastuti (Jurnal Warta Dharmawangsa, 2024)
Bodycam technology is used by the leadership of the Korlantas Polri to supervise members of the highway patrol (PJR) by installing a high-tech portable camera on the member's body which functions to record all activities while on duty. The implementation of this supervision needs to be evaluated with the aim of knowing the effectiveness and improving the program components. One of the evaluation models used is CIPP (Context, Indut, Process, Product), with the aim of research to increase supervision and optimize technology as a means of controlling leaders over members without having to be on site. By building a theory of program evaluation, supervision, human resource management as an analytical knife that is strengthened by the concept of traffic and bodycams. This study used a qualitative approach and field research research methods. Data collection techniques used interviews, observation, and document studies, as well as qualitative data analysis techniques. Sources of informants were the Head of Sub Directorate and PJR Korlantas Polri, Head of IT Korlantas Polri, Kasie PJR Korlantas Polri, Kaurmin PJR, Head of Main PJR, Main Personnel of PJR and Command Center Personnel. The results of the research show that in context evaluation, there is no legal basis governing program implementation. Evaluation of inputs, it is necessary to increase the knowledge and skills of members, program facilities and infrastructure and effective and efficient use of the budget. Process evaluation, SOP and program implementation schedule have not been formulated. Product evaluation has been achieved but not optimal. In conclusion, each CIPP component has been running quite well, but it is necessary to increase the quality and quantity of each aspect so that the program objectives are achieved. Keywords: program evaluation, CIPP, supervision